Contemporary financial intermediation - Greenbaum, Stuart I. (Academic Press advanced finance series., 2007)
Stuart Greenbaum and Anjan Thakor bring a unique analytical approach to the subject of banks and banking in this completely revised and updated new edition. They expand the scope of the typical bank management course by addressing all types of deposit-type financial institutions and by explaining the why of intermediation rather than simply describing institutions, regulations, and market phenomena. This analytic approach strikes at the heart of financial intermediation by explaining why financial intermediaries exist and what they do. Specific regulations, economies, and policies will change,